(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to determine the nature of the effect of long . term finance with Net profit which get by the organization from a grubs of finance sources which the organization can choose among them to funding its operations it is one of the basic necessities Net income . Despite this importance , however there is a distinct lack of many Iraqi organizations in the study of the relationship effect of between these two variables and this the reaserch problem . The data of research were obtained the annual guide of Iraqi market for securities where a data of sample of Iraqi Banks was selected which were five banks from 2004 to 2007 , most of the analysis results confirmed that there is an inverse relationship between the long-term finance and Net profit so the researcher concluded that the sources of the long-term finance is less profitability than other sources of funding and the researcher recommended with the necessity of organizations to balance between different funding sources and to study the positives and negative of each source before choosing their sources of funding.